Effect of seed pre-treatments on germination of ashwagandha (Withania somnifera) - PREETI; S.K. JAIN; D.K. JAIN; H.C.S. NEGI (Seed Research, 2026)
Effect of seed pre-treatments on per cent germination of different seed lots of ashwagandha (Withania somnifera Dunal) among various physical and/or chemical treatments applied, pre-washing the seeds in running water under laboratory ambient temperature increased this germination values due to removal of certain inhibiting chemicals accumulated in seed coat. Thus, pre-washing seed treatment in running water for ashwagandha ranked as the best followed by application of gibbrellic acid. Seed dormancy was due to certain chemicals present in seed coat, as pre-washing of seeds enhances seed germination. Pre-washing of ashwagandha seeds in running water, under laboratory ambient temperature ranked as the best, eco-friendly and economical.